Emotional competencies and entrepreneurial intention: An extension of the theory of planned behavior case of Ecuador - Oswaldo Verdesoto Velástegui (Taylor & Francis Group, 2021)
This study analyzes the relationship between emotional competencies and entrepreneurial intention of students from public higher education institutions in Ecuador, supported by an extended model of Ajzen’s Theory of planned behavior. The results are derived from a questionnaire applied to students of last semester of careers with academic business training. To analyze the results, structural equation modeling (SEM) was used. The findings show that emotional competencies are significant factors in the configuration of entrepreneurial intentions and have a direct and positive relationship with the cognitive antecedents of entrepreneurial attitude and self-efficacy. It is suggested that students with a higher degree of emotional competencies cope in a better way with the cognitive bias that can make it difficult to recognize business opportunities. The main contribution of this study was to give generality to the results that have been obtained in the use of emotional competencies to promote the intentionality of entrepreneurship in the context of emerging economies.